Pengaruh Keunggulan Produk dan Keunggulan Layanan terhadap Keputusan Pembelian Konsumen di CV. Pucuk Daun Lestari - M. Wahab Khasbulloh; Muammar Afif Al Qusaeri; Muthi’atul Khasanah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to describe the effect of product excellence and service excellence on consumer purchasing decisions at CV Pucuk Daun Lestari. The population in this study were all consumers of CV Pucuk Daun Lestari totaling 1,320 consumers. The number of samples for research uses a margin of error of 2.5% of the total sample, namely 92 consumers. The sampling technique used is incidental sampling method. The data collected was carried out using questionnaires and interviews which were then analyzed using validity tests, reliability tests, and linear regression analysis. The results showed that there was a positive and significant influence between the variables of product excellence and service excellence and service excellence on consumer purchasing decisions at CV Pucuk Daun Lestari, either jointly or partially.